Broadband Dipole-Loop Combined Nanoantenna Fed by Two-Wire Optical Transmission Line. (28th February 2017) - de Souza, Janilson L.; da Costa, Karlo Q.; Dmitriev, Victor; Bamberg, Felipe
Abstract : This paper presents a broadband nanoantenna fed by a two-wire optical transmission line (OTL). The antenna is defined by a combination of a dipole and a loop, where only the dipole element is connected to the OTL. The analysis is fulfilled by the linear method of moments with equivalent surface impedance to model the conductors. Firstly, the nanoantenna alone is investigated, where the input impedance, current distribution, reflection coefficient, fractional bandwidth, radiation efficiency, and radiation pattern are analyzed. Then, the input impedance matching of this antenna with the OTL is considered. In this case the current, near field distribution, radiation pattern, and reflection coefficient are calculated for different geometrical parameters. The results show that the loop inserted in the circuit can increase the bandwidth up to 42% and decreases the reflection coefficient in the OTL to −25 dB.